Standard ultra-staging compared to one-step nucleic acid amplification for the detection of sentinel lymph node metastasis in endometrial cancer patients: a retrospective cohort comparison. Issue 3 (March 2020) - Fanfani, Francesco; Monterossi, Giorgia; Di Meo, Maria Letizia; La Fera, Eleonora; Dell'Orto, Federica; Gioè, Alessandro; Lamanna, Maria; Ferrari, Debora; De Ponti, Elena; Perego, Patrizia; Restaino, Stefano; Carlo, Ronsini; et al.
Abstract : Introduction: The objective of this study was to compared standard ultra-staging (SU) with one-step nucleic acid amplification (OSNA) for the detection of sentinel lymph node (SLN) metastasis in women with apparent uterine-confined endometrial cancer. Methods: All women underwent SLN identification with complete surgical staging. All SLNs were cut perpendicular to the long axis and two adjacent 5 µm sections were cut at each of two levels 50 µm apart. At each level, one slide was stained with hematoxylin and eosin and the other with immunohistochemistry using the AE1/AE3 anti-cytokeratin antibody, as well as one negative control slide for a total of five slides per block. For OSNA analysis, the 2 mm sections of the lymph nodes were homogenized to form a lysate. The lysate was then centrifuged and inserted into the RD 100i instrument where the isothermal amplification of CK19 mRNA was executed. Results: Of the 396 patients included in the retrospective analysis, 214 were in the SU group, and 182 in the OSNA group. Overall 869 SLNs were identified (490 SU, 379 OSNA). Sixty patients exhibited SLN metastasis (34 SU, 26 OSNA). Macrometastasis, micrometastases, and isolated tumor cells (ITC) were 5.1%, 4.1%, and 0.2%, respectively, in the US group, and 2.4%, 6.3%, and 0.1%, respectively, in the OSNA group (p=0.022). Conclusions: The OSNA assay detected a higher rate of micrometastasis and a lower rate of macrometastasis and ITC when compared with SU. The clinical and prognostic impact of ITC is debatable and controversial. Further studies are needed to clarify the respective roles of the OSNA and SU methods, and the possible role of ITC in the prognosis of patients with apparent early-stage endometrial cancer.